Levels of sulfur effects on alfalfa production and mineral composition - Moreira, Adônis; Guedes de Carvalho, Janice; Evangelista, Antônio Ricardo (Pesquisa Agropecuaria Brasileira, 1997)
The sulfur (S) effect on alfalfa production and mineral composition was studied in plastic pots of five liters of soil Oxisol (Dark-Red Latosol dystrophic). The experimental design was completely randomized factorial scheme (4 x 6) with five replications. Four levels of sulfur (0, 25, 50 and 100 mg dm-3 of CaSO4.2H2O ) and one level of K2SO4 (50 mg dm-3 of S) in six cutting times, were studied. The analyzed variables were: dry matter production (DM) and amounts of crude protein (CP), P, K, Ca, Mg and S in the dry matter. The dry matter production and the P and S levels varied according to the sulfur dosage and the cutting time. The highest DM levels were observed with the 100 mg dm-3 of S treatment, and the lowest with the one that did not receive S. The last two samples showed the lowest production, probably due to the nutrient extraction. The levels of S raised with sulfur application and diminished in the last cuttings. The opposite was observed with the level of P indicating a diluting effect or a negative interaction between P and S. The levels of CP, K, Ca and Mg varied according to the cutting number.